The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/9794575
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccine Treatment in Dogs Experimentally Infected with Trypanosoma cruzi

Abstract: Chagas disease is a chronic and potentially lethal disorder caused by the parasite Trypanosoma cruzi, and an effective treatment has not been developed for chronic Chagas disease. The objective of this study was to determine the effectiveness of a therapeutic DNA vaccine containing T. cruzi genes in dogs with experimentally induced Chagas disease through clinical, pathological, and immunological analyses. Infection of Beagle dogs with the H8 T. cruzi strain was performed intraperitoneally with 3500 metacyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…An additional challenge is that the large majority of vaccine studies described above focus on mouse models, and the extent to which the strong vaccine immunogenicity and efficacy observed can be extrapolated to humans remains unknown. Studies in dogs have shown promise in reducing the T. cruzi parasite burden [ 86 , 87 , 88 , 89 , 90 ], but their limited scope does not provide sufficient evidence supporting vaccine efficacy to delay or prevent cardiac dysfunction. Infectiousness of dogs may nonetheless be reduced by vaccination [ 91 ].…”
Section: Challenges and The Way Forwardmentioning
confidence: 99%
“…An additional challenge is that the large majority of vaccine studies described above focus on mouse models, and the extent to which the strong vaccine immunogenicity and efficacy observed can be extrapolated to humans remains unknown. Studies in dogs have shown promise in reducing the T. cruzi parasite burden [ 86 , 87 , 88 , 89 , 90 ], but their limited scope does not provide sufficient evidence supporting vaccine efficacy to delay or prevent cardiac dysfunction. Infectiousness of dogs may nonetheless be reduced by vaccination [ 91 ].…”
Section: Challenges and The Way Forwardmentioning
confidence: 99%
“…It should be noted that a limitation in a large part of the vaccine candidates evaluated is that they have been mainly tested in murine models, so it is unknown whether this observed efficacy is similar in humans. This leads to the use of other animal models, such as dogs [115], non-human primates [25], as well as the cellular response in chagasic patients [20], and mixed therapy trials have been carried out where low-dose chemotherapeutic treatment is combined with the application of vaccines [4], which in some cases it reduces heart disease [21] in others oxidative damage is controlled, observing a cardioprotective effect [116][117][118].…”
Section: Therapeutic or Prophylactic?mentioning
confidence: 99%
“…Vaccination is the cheapest strategy to prevent infectious diseases and a commercial Submit your Manuscript | www.austinpublishinggroup.com vaccine against ChD is not yet available. Multiple vaccine prototypes have been tested and have shown to be good candidates in terms of protection and with great advantages for their production and application [19][20][21][22][23][24]. During infection, the immune response that is generated against the parasite is not enough to neutralize and/ or eliminate it, this being the main factor in the persistence of the parasite as well as the development of the chronic phase of the disease; where the parasite load and the unbalance of oxidative stress generate the damage in the host tissue [25], therefore, the control of T. cruzi by activating the immune system during the acute phase of the disease would prevent the development of the pathology [26].…”
mentioning
confidence: 99%
“…Both medications have potentially life-threatening adverse effects, resulting in repeated treatment pauses [ 14 , 15 , 16 ]. Previously, a study was conducted to determine the effectiveness of a therapeutic DNA vaccine containing T. cruzi genes in dogs with experimentally induced Chagas disease [ 17 ]. Additionally, because several new vaccination applications have been proposed, most vaccines produced for dogs have been modified [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a study was conducted to determine the effectiveness of a therapeutic DNA vaccine containing T. cruzi genes in dogs with experimentally induced Chagas disease [ 17 ]. Additionally, because several new vaccination applications have been proposed, most vaccines produced for dogs have been modified [ 17 ]. Its value associated with a prophylactic vaccination is clear and supported by several pre-clinical investigations, although specific performance and cost-effectiveness considerations must be addressed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%